Produção de conteúdos audiovisuais na formação inicial de professoras/es que ensinam Matemática - Miranda, Rebeca Souza de (Universidade Federal de São Carlos, 2025)
In this master's dissertation, we present the development of a research project linked to the Graduate Program in Education (PPGE) at the Federal University of São Carlos (UFSCar), within the research line "School Education: Theories and Practices". Based on experiences involving the production of audiovisual content in the Pedagogy course, the study aimed to analyze the potential contributions to teacher education, specifically in the teaching of mathematical content, through the appropriation of technological resources. The general objective was to analyze evidence of learning among undergraduate Pedagogy students (UFSCar) regarding their appropriation of technological resources, and to identify what applications/implications this appropriation may offer for initial teacher education within the context of the mandatory course "Mathematics: Content and Its Teaching". This was explored through an experience involving the production of audiovisual content (podcasts and videos) in the field of Mathematics Education for the early years of schooling. To this end, within a data production context based on a qualitative research approach of an analytical-descriptive nature, the study focused on experiences in two classes (morning and evening) of the aforementioned course, during the 6th semester (3rd year) of the second academic semester of 2023. The instructor of the course was also the advisor of this research. The proposal involved participant observation during in-person classes and specific guidance for subgroups to write scripts for recording mathematical videos and/or podcasts based on topics studied in class. This was followed by the initial production of content, feedback and final guidance, sharing of the materials on online platforms, and later class presentations, which allowed for reflection on the process and its effects on student teacher education. The data analysis indicates the importance of incorporating creative and original proposals using digital technologies into teacher education curricula — not in a reductionist manner, but rather as a means to foster spaces for experimentation and the construction of teaching knowledge. The production of these resources enabled an expansion of future teachers’ repertoires, allowing them to recognize the feasibility of replicating similar practices in their own professional work.
Production of audiovisual content in the initial training of teachers who teach Mathematics
Keywords: Tecnologia e recursos audiovisuais; Educação matemática; Curso de pedagogia; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO